2009
DOI: 10.1177/1352458508099479
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in MS: a study of conventional and nonconventional MRI measures

Abstract: There were no significant gender-related differences regarding nonconventional MRI measures. GM and central atrophy are more advanced in male patients, whereas WM atrophy is more advanced in female patients. These gender-related MRI differences may be explained by the effect of sex hormones on brain damage and repair mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 50 publications
9
61
2
2
Order By: Relevance
“…These results confirm those of previous studies which have suggested that males are more prone to MS brain damage [7,8] and/or that they show faster MS progression than females [3,4].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results confirm those of previous studies which have suggested that males are more prone to MS brain damage [7,8] and/or that they show faster MS progression than females [3,4].…”
Section: Discussionsupporting
confidence: 83%
“…Although being male has been proposed as a risk factor for cognitive impairment in MS patients [5], the results on brain neuropathological MS indices are conflicting, some studies have suggested a higher degree of brain damage in males [6][7][8], while others have failed to replicate these findings [9,10]. As these conflicting results might derive from gender interacting with other relevant demographic and clinical variables, we explored whether female and male MS patients, carefully matched for age, years of disease, level of education, intelligence quotient (IQ), neuropsychological performance and physical disability, differed in two indices of MS progression: gray matter (GM) atrophy and resting state functional connectivity (FC) changes.…”
Section: Introductionmentioning
confidence: 99%
“…Our results could thus suggest a promotion of repairing and neuroprotective mechanisms associated with OC use. This interpretation is supported by experimental and clinical data indicating that sex hormones may have protective effects on brain damage and repair mechanisms in these patients [3][4][5]. All oestrogens are not exactly alike [5,23].…”
Section: P-valuesupporting
confidence: 64%
“…A higher prevalence of women with the RR-MS and a female-specific increase in the incidence of the disease has been documented, mainly from an increase in the number of female patients with RR-MS [2]. Gender-related differences in clinical severity, immunological features and brain damage have also been reported, suggesting an effect of sex hormones [3,4]. Moreover, in mice with experimental autoimmune encephalomyelitis (EAE), the animal model of MS, treatment with sex hormones is able to protect against the development of the disease or reduce the severity of its clinical signs [5].…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, RRMS affects women about twice as often as men, and overall male gender has also been associated with worse prognosis. Although some small studies reported that men with MS are prone to develop less inflammatory but more destructive lesions than women (Pozzilli et al, 2003), have less T2 and gadolinium(Gd)-enhancing lesions (Weatherby et al, 2000) but more T1 lesions (van Walderveen et al, 2001) and more brain atrophy (Antulov et al, 2009), gender-specific MRI differences have not been confirmed by large studies (Fazekas et al, 2009). However, gender appears to influence disability during the early phase of RRMS.…”
Section: -Discussionmentioning
confidence: 99%